2011
DOI: 10.1002/jso.21893
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the intramedullary diaphyseal segmental defect fixation system for bone tumors

Abstract: The modularity, ease of application and preservation of the adjacent joints are major advantages of segmental modular prostheses; however, the complications' rate is high. Complications occur most often at the proximal stem in femoral reconstructions and reconstructions for more than 10 cm length of bone resection. In these cases, the use of these implants should be reconsidered or not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 42 publications
6
72
0
Order By: Relevance
“…This study presents the functional outcomes of 44 reconstructive operations in 41 patients using a modular intercalary endoprosthesis. These results are comparable to similar studies involving intercalary endoprostheses and the inclusion of 41 patients (44 implants) from three musculoskeletal oncology centers makes this one of the largest studies to date using this type of reconstruction [1,2,9,10,18,24,31,33] (Table 3). This study has several limitations which bear discussion.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study presents the functional outcomes of 44 reconstructive operations in 41 patients using a modular intercalary endoprosthesis. These results are comparable to similar studies involving intercalary endoprostheses and the inclusion of 41 patients (44 implants) from three musculoskeletal oncology centers makes this one of the largest studies to date using this type of reconstruction [1,2,9,10,18,24,31,33] (Table 3). This study has several limitations which bear discussion.…”
Section: Discussionsupporting
confidence: 80%
“…Segmental resection of the diaphysis of a long bone allows preservation of joint function and in skeletally immature patients allows for preservation of the physes. Many surgical options for the resection, reconstruction, and stabilization of segmental intercalary defects have been described and include the biologic options of autografts [7,8,29], allografts [5,6,11,12,15,22,23,25,26], and distraction osteogenesis [13,36] or use of metal constructs including segmental intercalary endoprostheses [9,10,31] and, although less practical, custom implants [1,2,4,18,24,33]. There have been few reports that analyze functional outcomes after treatment with modular segmental intercalary endoprostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques for knee arthrodesis have been described, including the Charnley compression arthrodesis technique, Putti-Juvara technique, xenograft, external fixation, intramedullary nail with bone graft, intramedullary nail and cement, and segmental allograft [5-7, 12, 14, 21, 27, 28, 30, 35, 40]. Each technique has inherent disadvantages and can yield unpredictable and suboptimal results [5,6,9,30,40,48]. To provide improved and more uniform outcomes, modular prosthetic arthrodesis systems were developed [3,16,48].…”
Section: Introductionmentioning
confidence: 99%
“…This is important, as structural failure was also demonstrated in another study [6] using the same device with a similar high risk of complications in the femur, more specifically, in the proximal of the two stems. This raises the question whether intercalary endoprosthetic replacement for segmental defects is a viable option in the lower extremity, especially in the femur.…”
Section: Where Do We Need To Go?mentioning
confidence: 67%
“…Once integrated, allograft and autograft reconstruction permit full weight bearing and perhaps fewer long-term complications. Previously published studies reported the nononcological failure rate of these reconstructions as ranging from 14% to 50% at mid-term followup [1,2,[4][5][6].…”
mentioning
confidence: 99%